Black Aortic Valve: Incidental Finding of Alkaptonuria - Putz, Christina; Putz, Franz Josef; Keyser, Andreas; Schmid, Christof (The Thoracic and Cardiovascular Surgeon Reports, 2021)
Background Alkaptonuria is a rare autosomal recessive genetic disorder of tyrosine metabolism, which results in accumulation of homogentisic acid in various tissues, including the cardiovascular system.Case Description We report on a 64-year-old man with mixed aortic valve disease who underwent conventional aortic valve replacement. Intraoperative aortotomy revealed black pigmentation of the intima of the ascending aorta and the aortic valve was observed with thickened and calcified dark black leaflets. Histopathological diagnosis of ochronosis of the aortic valve was made.Conclusion Despite several previous signs and symptoms, the diagnosis of alkaptonuria was not established until aortic valve replacement.
Keywords: aortic valve; heart valve; cardiac